A mesoporous tin phosphate–graphene oxide hybrid toward the oxygen reduction reaction. Issue 42 (10th May 2017) - Pramanik, Malay; Li, Cuiling; Kaneti, Yusuf Valentino; Yamauchi, Yusuke
Abstract : We report a one-pot synthetic strategy for the production of an efficient oxygen reduction reaction (ORR) electrocatalyst by the hybridization of hexagonally ordered mesoporous/crystalline tin phosphate (mesoSnPi) nanoflakes with thin layers of graphene oxide (GO). Abstract : We report a one-pot synthetic strategy for the production of an efficient oxygen reduction reaction (ORR) electrocatalyst by the hybridization of hexagonally ordered mesoporous/crystalline tin phosphate (mesoSnPi) nanoflakes with thin layers of graphene oxide (GO). In the electrocatalytic measurements, the obtained nanocomposite (SnPi@GO) exhibited a superior electrocatalytic performance for ORR over mesoporous tin phosphate (mesoSnPi), bulk tin phosphate (bulkSnPi), bulk tin oxide (bulkSnO), various transition metal phosphate nanomaterials and most state-of-the-art manganese oxides.